Vocational and occupational counsseling: a strategy of preventive intervention directed to Young men and women from the interior of the province of Buenos Aires - Quiles, Cristina Haydée (Orientación y Sociedad.)
This work belongs to one of the activities that are carried out in the Vocational and Occupational Guidance Center (V.O.G.C.) of the Faculty of Humanities and Educational Sciences at the L.P.N.U. In the year 1994 the Vocational/Occupational Guidance Programme for Municipalities was created, destined for work with adolescents who are attending their last year at secondary schools in the interior of the Province of Buenos Aires . The Programme aims at fostering the development of spaces for reflection related to the educational/working projects of the adolescents who are close to entering university. The proposal is based on the methodology of work groups, in the journeys preoccupations are sheared, the worries and fears experienced by the students are shared with their hosts, possibilities are used as ground for construction, dealing both with aspects of their current situation and their future possibilities. From the analysis of the group productions collected throughout these years, we have developed a student's profile that - although it resembles the one obtained from local adolescents- adds new questions and points of view, thus increasing the complexity of the balance of forces related to the question of having to make a choice.